Analisis perlindungan hukum tindakan pencabutan konten secara Unilateral oleh Youtube berdasarkan Undang-undang Nomor 28 tahun 2014 tentang Hak Cipta - Andhika Justisia; Dyah Permata Budi Asri (Universitas Janabadra, 2020)
There are so many content creators that lost their video because of false claim using DMCA notice and takedown. When YouTube receive a report of copyright infringement using notice and takedown, YouTube must takedown that content video as soon as possible. There are three questions related to the problems. They are 1 How do the YouTube’s indicators related to copyright infringement look like reviewed using Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta 2 Are the content creators that lost their content video able to ask YouTube about the clarification of the copyright infringement 3 How is YouTube conduct reviewed using Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta. In order to answer those questions, the researcher used normative research as and secondary data sources. Then, the researcher explained the result of the research using qualitative descriptive. It showed that YouTube does not have copyright infringement indicators. When taking down a content video, YouTube is only using the description provided by the claimer. That conduct did not match the theory of legal certainty. For the content creators that lost their content videos can do an appeal by sending a counter notice and takedown and sending a restoration content request to YouTube. The opportunity that is given by YouTube to the content creators that lost their content was match with the theory of justice. Reviewed using Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta, YouTubes conduct is not violating any terms of that regulation.